The Next Chapter in the STEM Education Narrative: Using Robotics to Support Programming and Coding - Blackley, Susan; Howell, J. (2019)
In this paper, we use our qualitative research notes and observations to portray a model for integrated STEM education and summarise primary school students’ typical and recurring ways in which they engaged with each new robot. The purpose of this paper is two-fold: first, to unpack key elements of the Australian Curriculum: Technologies in order to support teachers and pre- service teachers to implement these components, and second, to describe ways in which teachers can teach authentic integrated STEM education that also provides opportunities for students to develop and demonstrate 21st century competencies. Based on data collected from projects undertaken in a number of school sites over 18 months, we have developed and share a model for the gradual structured release of teacher control over student activity in STEM activities, and describe how this concept can be a basis for in-situ teacher professional learning. The affordances of robotics and visual programming as a context for integrated STEM education are discussed, and identified as promoting “head-heart-hands” learning.